Flight science : mathematics, techniques, sensibility - Mayboudi, Layla S. (Mercury Learning and Information, 2019)
This book is intended for aviators or individuals who are interested in application of mathematics in aviation. A reader new to the field working towards their recreational, private, or commercial license and one already flying a single piston or multi-engine aircraft will both benefit from the content. The book covers aviation mathematics in a variety of subjects, from meteorology to flight mechanics, in an organized, easy-to-understand approach. The book may be used as a reference and includes examples with step-by-step solutions. The eventual goal is to make the flying experience a more enjoyable one by making the flight mathematics-related topics less daunting and more accessible to wider aviation fans. Features:" Covers mathematics related to a variety of topics including meteorology, flight performance, climbs, enroute, descents, fuel calculations, flight mechanics, weight and balance, take-off and landing calculations" Includes examples related to popular aircraft types" Includes examples with complete solutions and test samples